Anti-Metalloprotease P-I Single-Domain Antibodies: Tools for Next-Generation Snakebite Antivenoms - Silva, Marcela C. S.; Pereira, Soraya S.; Gouveia, Marilia P.; Luiz, Marcos B.; Sousa, Rosa M. O.; Kayano, Anderson M.; Francisco, Aleff F. [UNESP]; Prado, Nidiane D. R.; Dill, Leandro S. M.; Fontes, Marcos R. M. [UNESP]; Zanchi, Fernando B.; Stabeli, Rodrigo G.; et al. (Wiley, 2022)
In order to address the global antivenom crisis, novel antivenoms need to present high therapeutic efficacy, broad neutralization ability against systemic and local damage, sufficient safety, and cost-effectiveness. Due to biological characteristics of camelid single-domain antibodies (VHH) such as high affinity, their ability to penetrate dense tissues, and facility for genetic manipulation, their application in antivenoms has expanded considerably. VHHs that are active against the metalloprotease BjussuMP-II from the snake Bothrops jararacussu were selected. After isolation of BjussuMP-II, a camelid was immunized with the purified toxin in order to construct the recombinant phage library. Following a round of biopanning, 52% of the selected clones were able to recognize BjussuMP-II in an ELISA assay. After sequencing, seven sequence profiles were identified. One selected clone (VHH61) showed cross-reactivity to B. brazili venom, but did not recognize the Crotalus and Lachesis genera, indicating specificity for the Bothrops genus. Through in vitro tests, the capacity to neutralize the toxicity triggered by BjussuMP-II was observed. Circular dichroism spectroscopy indicated a robust secondary structure for VHH61, and the calculated melting temperature (TM) for the clone was 56.4°C. In silico analysis, through molecular docking of anti-BjussuMP-II VHHs with metalloprotease, revealed their potential interaction with amino acids present in regions critical for the toxin's conformation and stability. The findings suggest that anti-BjussuMP-II VHHs may be beneficial in the development of next-generation antivenoms.